The power reliability event simulator tool (PRESTO): A novel approach to distribution system reliability analysis and applications - Sunhee Baik; Juan Pablo Carvallo; Galen L. Barbose; Will Gorman; Cesca Miller; Michael Spears (International Journal of Electrical Power & Energy Systems)
The growing interest in onsite solar photovoltaic and energy storage systems is partially motivated by customer concerns regarding grid reliability. However, accurately assessing the effectiveness of PVESS in mitigating these interruptions requires a comprehensive understanding of location-specific outage patterns and the ability to simulate realistic scenarios. To address the gap, we introduce the Power Reliability Event Simulation TOol (PRESTO), the first publicly available tool that simulates location-specific power interruptions at the county level. PRESTO allows for a more realistic assessment of system reliability by considering the unpredictability and location-specific patterns of power interruptions. We applied PRESTO in a case study of a single-family home across three U.S. counties, examining the performance of a solar photovoltaic system with 10 kWh of battery storage during short-duration power interruptions. Our findings show that this system reliably met 93 % of energy demand for essential non-heating and cooling loads, fully serving these loads in 84 % of events, despite the constraints of daily time-of-use bill management which limits the battery’s state-of-charge reserve. However, when heating and cooling loads were included, system performance decreased significantly, with only 70 % of demand met and full service in 43 % of events. These results highlight the challenges of using solar photovoltaic and energy storage systems for short-duration outages, emphasizing the need to consider factors like battery size and grid charging strategies to improve reliability. Our study demonstrates the practical applications of PRESTO, providing valuable insights into potential mitigation strategies including grid charging and optimizing battery size.© 2017 Elsevier Inc. All rights reserved.